Is iron deficiency related with increased body weight? A cross-sectional study - Kaner, Gülşah; Pekcan, Gülden; Pamuk, Gülseren; Pamuk, Barış Önder; Amoutzopoulos, Birdem (Progress in Nutrition, 2016)
Aim: To investigate the relationship between iron deficiency and obesity through dietary intake and inflammation parameters in overweight and obese women. Material/Methods: A total of 619 women, aged 20-49 years with normal weight (n=170), overweight (n=179), and obesity (n=270) were involved in the study. The biochemical parameters [whole blood count (WBC), anaemia parameters, C-reactive protein (CRP), high sensitive C-reactive protein (hsCRP), soluble transferrin receptor (sTfR)] and bioelectrical impedance analysis were analysed one at the beginning of study. Results: Although dietary iron intake were higher in the overweight and obese groups, their WBC, CRP, hsCRP and sTfR levels were lower than women with normal weight (p<0.05). The percentage of iron deficiency in normal weight women was 23.5%, as it was significantly higher in obese and overweight women (45.6% and 41.9%, respectively). Conclusion: Iron deficiency risk can be more likely to occur in obesity due to increased level of inflammation. Therefore, physicians may need to give special attention to the assessment of iron status of obesity patients.